2013
DOI: 10.1063/1.4804821
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chosen extraterrestrial solar spectrum on clear-sky atmospheric absorption and heating rates in the near infrared

Abstract: Abstract:The extraterrestrial solar spectrum (ESS) is an important component in near infrared (near-IR) radiative transfer calculations. However, the impact of a particular choice of the ESS in these regions has been given very little attention. A line-by-line (LBL) transfer model has been used to calculate the absorbed solar irradiance and solar heating rates in the near-IR from 2000-10000 cm -1 (1-5 µm) using different ESS. For overhead sun conditions in a mid-latitude summer atmosphere, the absorbed irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…This controversy has primarily manifested itself in the solar physics literature, but it is of significant importance for the understanding of atmospheric processes, as SSI is a vital input into radiative transfer schemes used in climate and weather models, and in passive remote sensing systems such as MODIS (MODerate Imaging Spectroradiometer, Platnick & Fontenla, ; Thome et al, ). For example, Menang and Shine () found that using different NIR SSI from recent observations leads to ~8% differences in atmospheric absorption and heating rates. It is therefore important to measure the SSI as accurately as possible from a number of independent sources.…”
Section: Introductionmentioning
confidence: 99%
“…This controversy has primarily manifested itself in the solar physics literature, but it is of significant importance for the understanding of atmospheric processes, as SSI is a vital input into radiative transfer schemes used in climate and weather models, and in passive remote sensing systems such as MODIS (MODerate Imaging Spectroradiometer, Platnick & Fontenla, ; Thome et al, ). For example, Menang and Shine () found that using different NIR SSI from recent observations leads to ~8% differences in atmospheric absorption and heating rates. It is therefore important to measure the SSI as accurately as possible from a number of independent sources.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from Figure that these seven spectra differ in spectral resolutions, spectral shapes, and absolute levels. However, this work will only study on the effect of the absolute levels of the SSI, since the effects of spectral resolutions and shapes on atmospheric absorption and heating rates were found to be relatively small by Menang and Shine (). It can also be observed from Figure that the two most recent SSI (CAVIAR2 and SOLAR‐ISS solar spectra) are in quite good agreement.…”
Section: Data and Radiative Transfer Calculationsmentioning
confidence: 99%
“…In a similar study by Sun et al () using a larger number of SSI (five), significant differences were also obtained in heating rates in the ultraviolet, downward solar irradiances (from ultraviolet to near IR), and changes in latitude‐height cross sections of zonal‐mean temperature. The only investigation dedicated to near IR wavelengths is that of Menang and Shine () in which they demonstrated that using different SSI in LBL radiative transfer calculations results in up to 8% differences in clear‐sky absorption and heating rates for a MLS atmosphere. However, the work of Menang and Shine () was limited to only two observed and two modeled SSI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations